Marketing performance measurement in B2B service companies : a multiple case study - Korhonen, Anna (My University, 2019)
Prior research has recognised the positive relationship between an organisation’s ability to control marketing activities through marketing performance measurement (MPM), and the attainment of that organisation’s marketing and business performance goals. Although the positive relationship between marketing activities and financial outcomes is currently widely accepted, marketing practitioners have found it difficult to measure and communicate the value of marketing to top management and others in the organisation. Still, empirical research has provided surprisingly little evidence of the key contingencies that can affect the successful application of MPM. Moreover, the majority of the marketing performance measurement research is only derived from business-to-consumer (B2C) markets. The purpose of this research is thus to understand the factors that affect the successful application of marketing performance measurement in B2B service companies. This issue is examined empirically through a qualitative case study approach. The data was collected through semi-structured theme interviews with 12 marketing and sales decision-makers having at least moderate MPM experience. The interviewed individuals work in 10 case companies operating in different industries in the B2B service field. Further, 6 exploratory expert interviews were carried out to improve the preliminary understanding of the phenomenon under study and also to facilitate in the choosing of the case companies and the key informants within these selected companies. This study finds that there is no typical MPM process. Instead, the MPM process should always be adopted to fit the company specific context. In the context of B2B service companies, 5 industry level factors and 9 corporate level factors were found to influence the successful application of MPM.
Keywords: marketing performance measurement, B2B marketing, service companies